Pengembangan Aplikasi Penanggulangan Bencana Ship, Handle & Drive Berbasis Android dan Web - Efri Tri Ardianto; Alinea Dwi Elisanti; Bakhtiyar Hadi Prakoso (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The development of information technology in the world is very fast, one of which is Mobile technology. Mobile is a cellular communication tool that provides convenience in conveying information quickly and completely so that it is very important for all sectors, especially in the service of government agencies. Indonesia is a country with a fairly high incidence of disasters. This condition cannot be separated from geographical factors, namely archipelagic and volcanic countries. There were 13 disaster events recorded in 2020. Jember Regency is an area where disasters often occur so that special attention is needed in handling them. There were 286 disaster events in 2019 including floods, landslides and earthquakes. There are many researches on making android applications about disasters, but they still focus on mitigation and have not fully touched the real needs of victims. So it is still necessary to develop the android application (Ship, Handle & Drive). This application adopts and develops an online motorcycle taxi system that is applied in disaster management by supporting the features needed in the current digital era, namely victims of natural disasters, the government and officers so that they are practical in use. the hope is that this application can facilitate disaster management easily, quickly, precisely and accurately. The research method uses the waterfall method with a systematic approach through the stages of Analysis, Design, Coding, and Testing.